PEMBINAAN KENAKALAN SISWA (STUDI SITUS SMA NEGERI 1 JOGONALAN KLATEN) - SUDIYONO , KAWIT (2011)
Modern societies with all of their complexities as the technology development products; mechanism, individualism, and migration to cities created a lot of social problems. Such kind of situation caused social patologic and sociopatic attitudes diverging from general norms. The more increasing and the easier way of getting information about sex as well as the faster information spreading caused teenagers did sexual behavior without getting married. The main focus of this research was ”how was the students delinquency construction of Jogonalan 1 senior high school in Klaten.” This research aimed to: (1) Describe the sexual behavior of Jogonalan 1 senior high school students; (2) Explain where the students of Jogonalan 1 senior high school do the sexual behavior; (3) Describe the character construction of the students of Jogonalan 1 senior high school acting sexual behavior. The analysis technique used was the qualitative descriptive one while the data gathering techniques used in this research were observation and interview. The research finding and discussion showed that there were the same characteristics when the students counducted sexual behavior. They were: (1). Students sexual behavior, the students implemented various kinds of sexual behavior such as: (a) watching porn scenes, (b) holding the chin and speaking anything about sex, (c) holding the sexual organ and asking to do intercourse, (d) holding the buttock, (e) looking for fun in order to touch the girl’s breasts, (f) locking the girl in a class to touch her breasts, (g) masturbating by using a condom, (h) masturbating by using fingers; (2). The students did their sexual behavior in the following places: (a) at school areas; (b) at home; (c) at the tourism places, villas, or hotels; (d) at quiet places such as at their quiet friend’s house, bedroom, school canteen, temple, classroom, and tourism places. (3). The students sexual behavior building was implemented through inviting both the students doing sexual behavior themselves and their parents, guiding them individually or in a group, and giving sanction toward they who repeat their sexual behavior, that was not to move them to the next grade or firing them from Jogonalan 1 senior high school.